Transplantation of Cold Stored Porcine Kidneys After Controlled Oxygenated Rewarming. Issue 6 (1st April 2018) - Gallinat, Anja; Lu, Jing; von Horn, Charlotte; Kaths, Moritz; Ingenwerth, Marc; Paul, Andreas; Minor, Thomas
Abstract: The concept of "controlled oxygenated rewarming" (COR) using ex vivo machine perfusion after cold storage was evaluated as tool to improve renal graft function after transplantation. Renal function after 20 min warm ischemia and 21 h cold storage was studied in an auto‐transplant model in pigs (25–30 kg, n  = 6 per group). In the study group, preimplant ex vivo machine perfusion for 90 min was added after cold storage, including gentle warming up of the graft to 20°C (COR). Kidneys that were only cold stored for 21 h served as controls. In vivo follow up was one week; the remaining native kidney was removed during transplantation. COR significantly improved cortical microcirculation upon early reperfusion and reduced free radical mediated injury and cellular apoptosis. Post‐transplant kidney function (peak levels in serum) was also largely and significantly improved in comparison to the control group. A weak inverse correlation was found between renal flow during COR and later peak creatinine after transplantation ( r 2  = 0.5), better values were seen for oxygen consumption, measured during machine perfusion at 20°C ( r 2  = 0.81). Gentle graft rewarming prior to transplantation by COR improves post‐transplant graft outcome and may also be a valuable adjunct in pretransplant graft assessment.